Adenomatoid Odontogenic Tumor of Anterior Maxilla; A Case Report. Issue 2 (December 2019) - Uppal, Ashish; Singh, Gaurav; Mishra, Madan; Gaur, Amit
Here, we report a case of adenomatoid odontogenic tumor in anterior maxilla in a young girl aged 14 years. Adenomatoid odontogenic tumor is a rare, benign, and distinct slow-growing odontogenic neoplasm which results in painless expansion of jaws. It usually occurs in the anterior maxilla followed by posterior maxilla and rarely in the mandible with an age range of 3 to 82 years and a relative frequency of 2.2% to 7.1% and showing a female predilection (1.9:1).